Peranan Etika Terhadap Motivasi Pegawai Pada Dinas Pendidikan Kabupaten Pelalawan - IRIYANTI, ENDANG; ", ERNAWATI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research is motivated by a problem that is still not optimal role of ethics on employeemotivation in performing the tasks that have not been as expected community . The purpose ofthis study to determine the role of the Ethics Office of Education Employee MotivationPelalawan . To determine the factors that influence employee motivation Role of Ethics of theEducation Department Pelalawan .The benefits of research for the author to add to the stock of knowledge in applying knowledgethat has been acquired in college in the real working world . While the practical benefits as asource of information about the role of the Ethics Office of Education employee motivationPelalawan As a further benefit of the scientific material to increase knowledge or can be anadditional intake of knowledge about the role of the Ethics Department of Education employeemotivation Pelalawan . Role of Ethics Against Employee Motivation includes three things: TrustWorthy , Responsibility , Honesty . The population and the respondents in this study is the Headof Department , Head of Public and Civil Service , Employees , and Visitors ( users of services)at the Department of Education Pelalawan .For teknil Snowball sampling using sampling . Sources and types of data namely primary andsecondary data . Data collection techniques include observation , interviews , literature study .Keywords : Ethics , Motivation , Employee